Academia-industry mobility in Malaysia: Realities and implications for leadership development programs - Vincent Pang; Lai, Yew Meng; Norzaini Azman; Wardatul Akmam Din; Anantha Raman Govindasamy (2020)
This article presents the current academia-industry mobility (AIM) situation in Malaysia with emphasis on the progress in the AIM agenda, factors affecting AIM, drivers of AIM, and barriers and constraints faced by AIM in the country. Using qualitative methods, 29 research participants consisting of university top management members, leaders of university-industry relations office, key industry players and lectures took part in the qualitative study. Main findings indicated that perceived unclear policy and guidelines related to AIM have further exacerbated what is already an unfavourable relationship between Malaysian public universities and industry players. Malaysian public universities were found to be slow in responding to the needs of industry players, whilst at the same time, the latter remained skeptical regarding the capabilities of the former. This article concludes by proposing a leadership development program framework that addresses AIM issues. Copyright of Journal of Institutional Research South East Asia is the property of South East Asian Association for Institutional Research and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract.